Quantitative biosciences dynamics across cells, organisms, and populations - Weitz, Joshua S.; Dominguez-Mirazo, Marian (Princeton University Press, 2024)
"This guide accompanies the textbook Quantitative Biosciences, providing students with the skills they need to translate biological principles and mathematical concepts into computational models of living systems. This hands-on guide uses a case study approach organized around central questions in the life sciences, introducing landmark advances in the field while teaching students-whether from the life sciences, physics, computational sciences, engineering, or mathematics-how to reason quantitatively in the face of uncertainty"-- Provided by publisher.